2012
DOI: 10.12806/v11/i2/rf2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Leadership: An Examination of College Students’ Understandings of the Concept of Leadership

Abstract: Incoming first-year college students (N = 4,292) were surveyed regarding attitudes and beliefs about leadership. Students' opinions about their leadership ability were high and were related to having an outgoing personality, as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 61 publications
8
47
1
Order By: Relevance
“…This hypothesis tested whether or not students that were in the younger age group of 18-20 would show more leadership growth at the end of the semester when compared to those ages 21 or older. This hypothesis is in line with Haber's (2012) study that showed age is a significant mediating factor for undergraduate students' leadership development.…”
Section: Purposesupporting
confidence: 89%
See 3 more Smart Citations
“…This hypothesis tested whether or not students that were in the younger age group of 18-20 would show more leadership growth at the end of the semester when compared to those ages 21 or older. This hypothesis is in line with Haber's (2012) study that showed age is a significant mediating factor for undergraduate students' leadership development.…”
Section: Purposesupporting
confidence: 89%
“…Similarly, Astin (1993) also showed that gender was a significant predictor in a host of college outcomes, including leadership development. Haber's (2012) study also showed that women demonstrated more contemporary understandings of leadership than men. These studies suggest women may possess a leadership advantage while functioning in this newer, post-industrialized model.…”
Section: Leadership Development and Gendermentioning
confidence: 66%
See 2 more Smart Citations
“…Its intent is that the results of the first, qualitative method can help develop or inform the second quantitative method (Greene, Caracelli, & Graham, 1989). Some thoughts need to be specified to the relationship between the initial qualitative outcomes and the design of the middle quantitative stage, whether this stage takes on developing or amending a tool or survey (Clark, Shahrouri, Halasa, Khalaf, Spencer, &Rose, 2012); keeps on generating new variables (Haber, 2012), consists of typologies, or conceptual models ,specifies activities for an intervention ; or involves crafting a website, an app, or a virtual reality program for testing (Ruffin, Creswell, Jimbo, & Fetters, 2009).…”
Section: Exploratory Sequential Designmentioning
confidence: 99%